Introduction to Communication Networks. - Anttalainen, Tarmo (Artech House, 2014)
This new book is an introduction to modern communications networks that now rely far less on telephone services and more on cellular and IP networks. The resource is designed to provide answers to the fundamental questions concerning telecommunications networks and services. This includes the structure and main components of a modern telecommunications network; the importance of standardization; and how cellular mobile networks operate; among many others. In addition, you are provided with problems and review questions to work though and help you master the material.